Leadership Literacy Challenges and Sustainable Transformation in Nigeria - Aderogba, Kofo A (Universitas Medan Area, 2025)
The public education system faces several challenges in providing quality literacy education. The work focuses on the role of adult leadership literacy education in achieving sustainable socioeconomic development, exploring how it can be utilized to promote sustainable development. The human condition can be described in terms of the threats to sustainable socioeconomic development, as shaped by the literacy level of Nigerian adult leaders. Like most of the African States, Nigeria is still